Delayed bilateral facet dislocation at L4-5: A case report. Issue 38 (September 2018) - Park, Hyung-Youl; Ha, Kee-Yong; Kim, Young-Hoon; Kim, Sang-Il; Min, Hyung-Ki; Oh, In-Soo; Seo, Jun-Yeong; Chang, Dong-Gune; Alhazmi, Mohammed Ali; Cho, Joon-Hyung
Abstract: Rationale: Traumatic bilateral facet dislocation in the lumbar (L) spine has rarely been reported. All reported cases were presented with acute facet dislocation. However, we present the first case of delayed bilateral facet dislocation at L4-5. Patient concerns: A 34-year-old woman presented with back pain after a head-on collision. The patient was treated conservatively for 3 months with rigid orthosis and activity restriction. Even after this conservative treatment, she continued to suffer from persistent back pain that radiated down her left leg and a progressively kyphotic posture. Diagnoses: Initial imaging studies revealed a fracture of the left L5 superior articular process with a posterior ligament complex (PLC) injury. Subsequent radiographs showed the locked facet dislocation with kyphotic changes. Interventions: The patient underwent surgical reduction and fusion, and the operative findings revealed the L4-5 bilateral facet dislocation and rupture of the PLC at the index level. Outcomes: After surgical reduction and fusion at L4-5 by posterior interbody fusion, we achieved a satisfactory clinical outcome. Lessons: Injury of the PLC in the lower lumbar region deserves careful attention for the development of sequelae. The anatomic transition from lordosis to kyphosis, in the lumbosacral region may be related to this type of injury.